The relationship between career guidance, parents and PTPTN loan on students' career choices / Muhammad Syazwan Sukry - Sukry, Muhammad Syazwan (Academy of Contemporary Islamic Studies, 2018)
Choosing a career right after graduation can be a difficult decision for anyone. Meticulous efforts need to be poured into making a life-changing decision. However, these decisions may be influenced by several factors. This study sought to investigate how career guidance, parents and PTPTN loan influence students' career choice. Conducted through a quantitative approach with the target respondents of Academy Contemporary Islamic Studies Faculty students in UITM Shah Alam that are currently on the final year of semester 6 and 7 in undertaking Bachelor Degree in Muamalat.